Religius Radikal: Ekspresi Gen-Z dalam Kesadaran Beragama dan Aktualisasi Ketaatan di Kalimantan Selatan - Noor Hasanah; Huriyah (Pascasarjana UIN ANTASARI Banjarmasin, 2023)
The interpretation, understanding, and practice of Islam have always been subject to diversity, with some adherents adopting a rigid, textual, and even